Seroprevalence of Neutralizing Antibodies against Human Adenovirus Type-5 and Chimpanzee Adenovirus Type-68 in Cancer Patients - Zhao, Hua; Xu, Can; Luo, Xiaoli; Wei, Feng; Wang, Ning; Shi, Huiying; Ren, Xiubao (Frontiers in Immunology, 2018)
Since the preclinical results about chimpanzee adenovirus serotype-68 (AdC68) based vaccine showed an encouraging results, it reminded us AdC68 may be a suitable cancer vaccine vector. Previous study indicated that the seroprevalence of NAbs against adenovirus was different between cancer patients and healthy volunteers. Knowledge regarding the prevalence rates of AdC68 NAbs for cancer patients is lacking. Therefore, assessing the pre-existence of Nabs against AdC68 in cancer patients could provide useful insights for developing future AdC68-based cancer vaccines. In this study, 440 patients with different pathological types of tumors and 204 healthy adult volunteers were enrolled to evaluate the NAbs against AdC68 and human adenovirus serotype-5 (AdHu5). The seroprevalence of NAbs against AdC68 was much lower than that against AdHu5 in cancer subjects (43.64% vs. 67.05%, P<0.01). The seroprevalence rates of NAbs to AdC68 in the cancer subjects were statistically higher than those detected in the healthy adult volunteers (43.64% vs. 23.53%, P=0.000). The seroprevalence rates of AdC68 NAbs were much lower in lung, laryngeal, esophageal, and cervical cancer patients compared to oropharyngeal, colon, and rectal cancer patients. Furthermore, the seroprevalence rates of AdC68 NAbs were much lower in lung adenocarcinoma patients than in lung squamous cell carcinoma patients (35.00% vs. 70.00%, P<0.05). No significant difference in the AdC68 NAbs among patients with different clinical stages of cancer was detected. The percentage of NAbs against AdC68 was significantly lower than that against AdHu5 (P<0.05) in stage I, II and III cancer patients. No significant difference between the percentage of neutralizing antibodies against AdC68 and AdHu5 in the subjects with stage IV cancer was detected. The study also showed that very low NAb titers against AdC68 with respect to AdHu5 in both healthy subjects and cancer subjects, especially in lung, laryngeal, esophageal, gastric and cervical carcinomas. Also, the titer of NAbs against AdC68 was significantly lower than that against AdHu5 in the same clinical stage and age group (P<0.05). Taken together, the present study showed that Nabs against AdC68 is much lower than AdHu5.These results provided strong support for candidating AdC68 as a suitable vector of cancer vaccines.